Young People With Borderline Personality Disorder Have an Increased Lifetime Risk of Being the Victim of Interpersonal Violence. Issue 13 (July 2022) - Cavelti, Marialuisa; Thompson, Katherine; Betts, Jennifer; Fowler, Claire; Luebbers, Stefan; Cottton, Sue M.; Chanen, Andrew
This study aimed to examine the lifetime risk of being the victim of criminal or violent offenses among young people with borderline personality disorder (BPD) features (1-9 DSM-IV criteria). Demographic and diagnostic data from 492 outpatients who attended a specialist public mental health service for 15- to 25-year-olds between January 1998 and March 2008 were linked with offending data from a state-wide police database, collected between March 1993 and June 2017, in order to establish victimization history. This included information on criminal offenses perpetrated against these young people and intervention orders implemented to protect them from being victimized by another person's violent behavior. Logistic regression analyses, adjusted for sex and co-occurring mental state disorders, were conducted on n = 378 who had complete data (76.5% females). As hypothesized, BPD diagnosis and number of BPD criteria were both significantly associated with an increased risk of being the victim of a violent offense and the complainant of a family violence intervention order. Anger and impulsivity independently predicted a higher risk of being the victim of a violent offense, while unstable relationships, impulsivity, and affective instability independently predicted a higher risk of being the complainant of a family violence intervention order. No significant association was found between BPD and the risk of being the victim of a nonviolent offense. These findings indicate that young people with any BPD features (even below the DSM diagnostic threshold) are at increased risk for victimization by interpersonal violence. Moreover, this risk increases according to the number of BPD criteria. This issue needs to be addressed by prevention and early intervention programs (e.g., by working on self-assertion and interpersonal skills, taking into account the possible influence of previous traumatizing relationship experiences).